Acute effects of French contrast and post-activation performance enhancement on throwing, jump performance, and training load in handball players - Eler, N.; Eler, S.; Sentürk, A.; Gençoglu, C.; Akalin T. C.; Karaagaçli, S. (BMC Sports Science, Medicine and Rehabilitation, 2026)
This study aimed to investigate the acute effects of the Band-French Contrast Method (Band-FCM) and Band-Post-Activation Performance Enhancement (Band-PAPE) protocols on throwing velocity, countermovement jump (CMJ) height, and internal training load (RPE) in elite youth male handball players. A total of 23 athletes from the U18 national team voluntarily participated in the study. The experimental design included four sessions: an initial familiarization and band-1RM testing day, followed by three intervention sessions arranged in a Latin square design. The Band-PAPE protocol consisted of two sets of shoulder press actions performed at 90% band-1RM, incorporating 3-second isometric holds followed immediately by explosive concentric movements, followed by 4 min of passive recovery before performance testing. The Band-FCM protocol comprised three sets of upper-body isometric, dynamic, and plyometric exercises applied in a sequential structure. Throwing velocity (measured via radar), CMJ height (assessed using Optojump), and RPE (CR-10 scale) were recorded before and 2-4 min after the intervention. The significance level was set at a = 0.05. Results showed that the Band-PAPE protocol significantly increased throwing velocity (+ 5.6 km·h?¹) without elevating RPE. Both protocols induced moderate improvements in CMJ height; however, only Band-FCM significantly increased RPE. In conclusion, Band-PAPE may be suitable for pre-competition and in-game use (e.g., pre-match warm-up, halftime, and preparing substitute players) due to its performance benefits with minimal increase in internal load, whereas Band-FCM appears more appropriate as a training-oriented strategy for longer-term power development rather than acute performance enhancement.